A comparison of new and existing rootstocks to reduce canker of apple trees caused by Neonectria ditissima (Nectriaceae, Hypocreales) - Lucas A. Shuttleworth; Sonia Newman; Ioannis Korkos (CABI Agriculture and Bioscience)
Abstract The grafting of apple rootstocks on to scions confers benefits including reduced tree size/dwarfing for trellis based growing systems, increased tolerance to physiological stress, and pest and disease management. The current study investigated the effect of rootstock selection on canker and tree death using eight common rootstocks M9 337, M9 337 with Golden Delicious (GD) interstock, M9 EMLA, MM106, M116, M26, Geneva® G11 and G41, in addition to six advanced selections from the NIAB East Malling apple breeding programme EMR-001—EMR-006, all grafted with Gala scions. One of the rootstocks, M9 377 was also grafted with a GD interstock. Two locations in England were selected, the first at East Malling, Kent, the second, at Newent, Gloucestershire. Several variables were analysed including cumulative numbers of dead trees per rootstock from 2017 to 2020, number of rootstock ‘A type’ cankers, number of scion mainstem ‘B type’ cankers, and number of peripheral ‘C + D + E’ branch cankers at the Kent and Gloucestershire locations in the fourth and final assessment year of 2020. Kendall’s rank correlation was used to test if trunk circumference (a measure of tree vigour) and canker were statistically dependant. Results showed that in Kent, there were significant differences between rootstocks for scion B cankers and peripheral C + D + E cankers. There were no significant differences found between rootstocks for rootstock A cankers at Kent, or any of the three canker types in Gloucestershire. There were up to 31.25% dead trees in Kent (EMR-004), and 30% in Gloucestershire (M9 337 with GD interstock, M26), but there were no significant differences in number of dead trees due to rootstock type in either Kent or Gloucestershire. The Kendall’s rank correlation analysis indicated there was almost no dependence of trunk circumference on canker. The three rootstocks with the overall lowest susceptibility to canker were M116, EMR-006, and EMR-004. The industry standard rootstocks M9 EMLA and M9 337 were ranked 12 and 14, and with EMR-001 were the three worst performing rootstocks. The Geneva® rootstocks G11 was ranked 6, and G41 was ranked 11. An interplay of factors are likely involved in the development of canker including location and environmental effects—rainfall, relative humidity, temperature, wind, soil type, topography, aspect, and other seasonal infection processes including pathogen inoculum load, and rainsplash of inoculum between trees and within individual trees, the genetics and physiology of each scion/rootstock combination, water and nutritional status of trees, hormonal and molecular signalling, and orchard management including pruning and removal of cankers.